Measurement of Radon-222 Concentration in Soil Samples of some Sulfuric Spring in Hit City Using CR-39 Detector - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
In this study, concentrations of radon were measured for seventeen samples of soil distributed in three Sulphuric Spring, in addition to other regions as a background in Hit City in AL-Anbar Governorate. The radon concentrations in soil samples measured by using alpha-emitters registration that emits from radon (222Rn) in (CR-39) track detector. The concentrations values were calculated by a comparison with standard samples. The results show that the radon concentrations in first spring varies from (258.253- 347.762 Bq/m3), second spring (230.374-305.209 Bq/m3), third spring (292.002-336.023 Bq/m3) and the average radon concentration in other regions (187.821 Bq/m3). As a conclusion of the study radon concentration in Sulphuric Spring is relatively higher than the background.